RANCANGAN BANGUN SISTEM INFORMASI PENDATAAN PEKERJA MIGRAN INDONESIA - Hatmoko, Bondan Dwi; Kusmanto, Tria Hadi (J-ENSITEC (Journal of Engineering and Sustainable Technology), 2021)
The huge impact on the advancement of data processing has been brought about by the development of information technology. from time efficiency, effectiveness of functions and costs incurred to be lighter. There are many things to be aware of ranging from the suitability of data to reality and the effective and efficient level of time used when processing documents manually in managing the data of Indonesian Migrant Workers. Armed with aproach system approach and modular approach used and analysis using qualitative method conducted research in the development of the system in indonesian migrant workers company. While the collection of data to obtain the data and information needed is by interviews, observations, documentation, and literature studies. The design of the information system for data collection of Indonesian migrant workers is expected to make it easier for employees in the company to process the data of migrant workers by reducing handwritten notes on paper media and processing data more efficiently and providing protection against data that has been stored.